2017
DOI: 10.1128/aac.01735-16
|View full text |Cite
|
Sign up to set email alerts
|

A Naturally Occurring Single Nucleotide Polymorphism in a Multicopy Plasmid Produces a Reversible Increase in Antibiotic Resistance

Abstract: ColE1 plasmids are small mobilizable replicons that play an important role in the spread of antibiotic resistance in Pasteurellaceae. In this study, we describe how a natural single nucleotide polymorphism (SNP) near the origin of replication of the ColE1-type plasmid pB1000 found in a Pasteurella multocida clinical isolate generates two independent plasmid variants able to coexist in the same cell simultaneously. Using the Haemophilus influenzae Rd KW20 strain as a model system, we combined antibiotic suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 25 publications
5
40
0
Order By: Relevance
“…In others words they will be heteroplasmic to a different degree. Recent data from another ColE1 plasmid (pB1000 in Haemophilus influenzae ) shows heteroplasmic cells to have higher overall number of plasmid copies compared to cells that are monomorphic for the mutated plasmid (here, like in our case, the mutation leads to copy number increase) 58 . Thus the differences in the extent of heteroplasmy (a mutant-to-wild-type ratio within a cell) will lead to different plasmid copy numbers within the daughter cells.…”
Section: Plasmid Heteroplasmy Likely Prevents Alterations In Copy Numbersupporting
confidence: 51%
“…In others words they will be heteroplasmic to a different degree. Recent data from another ColE1 plasmid (pB1000 in Haemophilus influenzae ) shows heteroplasmic cells to have higher overall number of plasmid copies compared to cells that are monomorphic for the mutated plasmid (here, like in our case, the mutation leads to copy number increase) 58 . Thus the differences in the extent of heteroplasmy (a mutant-to-wild-type ratio within a cell) will lead to different plasmid copy numbers within the daughter cells.…”
Section: Plasmid Heteroplasmy Likely Prevents Alterations In Copy Numbersupporting
confidence: 51%
“…Previous reports showed that the biological cost of a single plasmid, including a ColE1 plasmid (18, 35), is proportional to its copy number in the host cell (19, 36). We measured plasmid copy number (PCN) of pB1000, pB1005 and pB1006 in all the strains using quantitative PCR (qPCR) (Table 1, Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…These plasmids replicate via two RNAs (16). Natural SNPs in these RNAs allow different ColE1-like plasmids to stably cohabit within the same cell (17, 18). If the plasmids bear antibiotic resistance genes, this cohabitation confers antibiotic multiresistance to the host bacteria (9).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, while we examined rescue via single mutations, if multiple mutations with different dominance were available, populations at different ploidy levels may tend to evolve via different pathways (43). Furthermore, while we exclusively considered chromosomal mutations, mutations on plasmids, particularly those with high copy number (44), should show similar effects, although segregation patterns and hence time to achieve homozygosity are likely to differ. Finally, models developed thus far have assumed constant ploidy, whereas future modeling efforts could incorporate the dynamically changing and environment-dependent nature of bacterial ploidy.…”
Section: Discussionmentioning
confidence: 99%